The Impact Of Students' Perceptions Of Green Accounting On Sustainable Career Decisions - Andi Risdayanti; Rismawati; Zikra Supri (Universitas Serang Raya, 2024)
The purpose of this study was to determine student perceptions and green accounting influencing sustainable career decisions. This type of research uses quantitative, with the data used is primary data sourced from distributing questionnaires directly to respondents using Likert scale measurements. The population used by class A students of the Faculty of Economics and Business, University of Muhammadiyah Paalopo. Data collection in this study used purposive sampling techniques to select samples and produced 133 samples. The data analysis method used in this study is using the help of IBM SPSS 25 software with various tests. The results showed that student perceptions did not have a significant effect on sustainable career decisions, while green accounting had a significant effect on sustainable career decisions.